(3GdLeQcI h GdJHGOd GdJLGQj (B: s (3eWHhYI HjOGZhLjI ehLgI dWdHI GdSfI GdKGdKI , bSe GdYdhe GdJLGQjI , JNUU JLGQI OhdjI (B/ s - (3aQGM, aQjGds; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eONd Gdi GdJLGQI GdNGQLjI , GdfXQjGJ GdeaSQI dbjGe GdJLGQI GdNGQLjI , GdJaGhV GdJLGQj h YbhO GdHjY h JbfjGJ Gdfbd GdOhdj , GdYHhQ h GdJQGejR h BdjGJ Jehjd GdJLGQI GdNGQLjI , GdGLQGAGJ GdLeQcjI , GdGUdGMGJ GdLeQcjI GdLRGFQjI aj Xd eNWW YUQfI EOGQI GdLeGQc (B2007-2013 (3h GdGUdGMGJ GdLeQcjI hab GdeNWW GdGSJQGJjLj ddLeGQc ddaJQI (B2016-2019 (3, GdGJaGbjGJ GdJLGQjI GdLRGFQjI GdLRGFQjI eJYOOI GdGWQGa (B. s
(3eQGLY U(B.99s
Keywords: (3GdJHGOd GdJLGQjs; (3GdJLGQI GdNGQLjIs; (3GdLeGQcs